9x+26+7x-17=(-3x)+5x

Simple and best practice solution for 9x+26+7x-17=(-3x)+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+26+7x-17=(-3x)+5x equation:


Simplifying
9x + 26 + 7x + -17 = (-3x) + 5x

Reorder the terms:
26 + -17 + 9x + 7x = (-3x) + 5x

Combine like terms: 26 + -17 = 9
9 + 9x + 7x = (-3x) + 5x

Combine like terms: 9x + 7x = 16x
9 + 16x = (-3x) + 5x

Combine like terms: (-3x) + 5x = 2x
9 + 16x = 2x

Solving
9 + 16x = 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
9 + 16x + -2x = 2x + -2x

Combine like terms: 16x + -2x = 14x
9 + 14x = 2x + -2x

Combine like terms: 2x + -2x = 0
9 + 14x = 0

Add '-9' to each side of the equation.
9 + -9 + 14x = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 14x = 0 + -9
14x = 0 + -9

Combine like terms: 0 + -9 = -9
14x = -9

Divide each side by '14'.
x = -0.6428571429

Simplifying
x = -0.6428571429

See similar equations:

| x-0.5x=18000 | | 2(3y+5)=3(5y+.3) | | x-.50x=18000 | | Log(9)4x-log(9)8=2 | | 5z^2+2x-3=0 | | 3x-11+x-8+x+8+2x+7+x=540 | | k=c+293k+20 | | 3x-11+x-8+x-8+2x+7+x=540 | | 3(3+c)=2(c+4) | | y=200+20x | | 90+x+23+3x+27=180 | | 5x-4=-6x-15 | | (2x-8)/-5=9 | | 10(x+8)=100 | | 9x-2/5 | | 4(-3x-10)=2(x+8) | | (2x-8)/-5=0 | | 7x-18=6x+3 | | 5(g-2)+6=6(g-4) | | 5(u+8)=7u+34 | | 4(c+2)=7c+4-3c+4 | | 3w-3x-y+6w+15x-7y= | | 1/3q-6=3 | | 40-5x=5(-5x+4) | | 3-10k=-3(5k+2) | | x^6+5=10 | | 5c+30c-2=7(5c+8) | | 8x-3y+13w-5y-4w+4x= | | 12+14=2x | | 80+2x+10+3x+10=180 | | y=12x^2+6x-6 | | 3z+2i=1+2z+1+i |

Equations solver categories